Cis- and Trans-Acting Expression Quantitative Trait Loci of Long Non-Coding RNA in 2,549 Cancers With Potential Clinical and Therapeutic Implications - Li, Wenzhi; Xu, Chaoqun; Guo, Jintao; Liu, Ke; Hu, Yudi; Wu, Dan; Fang, Hongkun; Zou, Yun; Wei, Ziwei; Wang, Zhong; Zhou, Ying; Li, Qiyuan (Frontiers in Oncology, 2020)
Many cancer risk loci act as expression quantitative trait loci (eQTLs) of transcripts including non-coding RNA. Long non-coding RNAs (lncRNAs) are implicated in various human cancers. However, the pathological and clinical impacts of the genetic determinants of lncRNAs in cancers remain largely unknown. In this study, we performed eQTLs mapping of lncRNA expression (elncRNA) in eleven TCGA cancer types and characterized the biological processes of elncRNAs in the setting of genomic location, cancer treatment responses and immune microenvironment. As a result, 10.86% of the cis-eQTLs and 1.67% of the trans-eQTLs of lncRNA were related to known genome-wide association studies (GWAS) cancer risk loci. The elncRNAs are significantly enriched for those which are previously annotated as predictive of drug sensitivities in cancer cell lines. We further revealed the downstream transcriptomic effectors of eQTL-elncRNA pairs. Our data specifically suggested that the genes affected by eQTL-elncRNA associations are enriched in the immune system processes (P = 1.52×10-9) and the constitution of tumor infiltrating lymphocytes. In ovarian cancer, the “rs34631313-AC092580.4” pair was associated with increased fraction of CD8+ T cells and M1 Macrophage; whereas in KIRC, the “rs9546285-LINC00426” pair was associated with increased fraction of CD8+ T cells and a decreased fraction of M2 macrophages. Our findings provide a systematic view of the transcriptomic impacts of the eQTL landscape of lncRNA in human cancers and suggest its strong potential relevance to cancer immunity and treatment.